The influence of cathodic potentials on the surface oxide layer status and tribocorrosion behaviour of Ti6Al4V and CoCrMo alloys in simulated body fluid. (June 2022) - Namus, Righdan; Rainforth, W.M.
Abstract: Ti6Al4V and CoCrMo alloys are important metallic materials in orthopaedics applications because of their excellent combination of corrosion resistance, mechanical properties, and biocompatibility. However, Ti6Al4V possesses poor wear resistance, and CoCrMo implants have been reported to release toxic ions in vivo. In addition, orthopaedics applications are subjected to corrosive media and cyclic stresses, increasing the likelihood of scratching the surface, removing the protective oxide film, and thereby causing cathodic polarisation of the system. The present work examined the material loss in tribocorrosion and the thickness and resistivity (status) of the oxide layer under different cathodic potentials. The cathodic polarisation conditions were chosen to reflect those that might be found in vivo. The results explicitly showed a different impact of the cathodic potentials on the tribocorrosion behaviour of the two materials. Highlights: The influence of cathodic potentials on the tribocorrosion behaviour and the oxide layer's thickness and resistivity of Ti6Al4V and CoCrMo alloys was studied. Permanent damage in the oxide layer was observed under some cathodic potentials for CoCrMo alloy but not for Ti6Al4V. Not all cathodic potentials can prevent corrosion contribution in tribocorrosion for Ti6Al4V, but they do for CoCrMo alloy. The specific wear rate K decreased when applying a small cathodic potential for Ti6Al4V, but it increased again with higher cathodic potentials. In contrast, all cathodic potentials gave the same reduction in K for CoCrMo alloy compared to OCP conditions.